Decomposing the effect of height on income in China: The role of market and political channels - Eiji Yamamura; Russell Smyth; Yan Zhang (Osaka University, Institute of Social and Economic Research (ISER), 2015)
It is well known that height is positively associated with earnings. Based on individual level data, this paper investigates the channels through which height influences income in China. Our first key finding is that taller people are more likely to become members of the Communist Party, resulting in an increase in their income level. We label this the height premium in earnings through the political channel. Second, controlling for the political channel of the height premium, height is positively associated with income in the labor market. We label this the height premium through the market channel. Third, the height premium in earnings through the market channel is larger than that through the political channel.
Keywords: J08; J24; P26; 330; Labor market; China; Height; Communist membership